ANALISIS PENGENDALIAN KUALITAS LAMINATING BOARD DI PT. TIMUR SELATAN PARE KEDIRI - Sihmawati, Rini Rahayu (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
A more tight and high business competition in domestic as well as international marketencourage the company gain better quality product. Consequently, it needs continous improvingeffort toward the process capability, human, machine and environment. It is realized by PT.Timur Selatan at Pare Kediri for it product. The frequent problems emerged are whether theproduct quality including widt, lengt and moisture content according the spesification, whetherthese are delinquencies then what action in needed for good quality.The Aim of this research are : 1). To know whether the product quality ( width, lengthand moisture content) fulfills the specification 2). to know whether is delinquency happened fromcontrol limit. 3). What action are needed for the delinquency improvment. While the purposedhypothesis is the product quality has fulfill the specification and statistic controlling limit.The research is conducted at PT. Timur Selatan Pare kediri, the research methodology isusing the primary data from direct observation and secondary data from company. The dataanalysis is done by applying Statistical Quality Control which uses control X and R chart.The result shows that for the width and moistureContent are in the specification except the length. While for the satistical control shows in controllimit for the length and moisture content except width. The process capability is low for length (0,5479) and mioisture content (0,4018), so it is necessary to increase the process capability.Besides the variable quality is also caused by human factor, machine and equipment.Kata kunci : laminating board, quality control, Control X and R chart